Collaborative Governance for Online Distance Learning: A Case of a Dental Health Program of the Ministry of Health Bandung - Heriyanto, Yonan; Broto, Mani Festati (KnE Social Sciences, 2022)
Online learning is a strategic policy that is expected to contribute to the sustainability of educational performance. However, this policy has not been able to optimally solve existing problems. Shortcomings of students in attaining skills from core competency courses and the lecturers’ limited ability to provide online learning are problems faced by the Bandung Polytechnic Diploma III Dental Health Study Program. This study employed a literature review approach. We compiled a comprehensive collection of relevant studies by identifying collaboration theories; this was strengthened by including research related to distance learning collaboration in the health sector associated with Poltekkes Bandung’s SWOT. The results of this study suggested that the problems faced by the Dental Health program can be overcome through strengthening collaborative governance. Poltekkes Bandung can issue a policy to collaborate with the Faculty of Dentistry; they can thereby tackle the problem of students achieving core competencies and improve the capacity of lecturers to provide teaching by collaborating with educational institutions that have consistently held online distance learning. Keywords: collaborative governance, distance learning, Poltekkes Bandung